Interaction of the anion [2-B10H9O(CH2)4O]− with secondary amines - E. Yu. Matveev; S. S. Novikov; V. Ya. Levitskaya; A. I. Nichugovskiy; I. E. Sokolov; K. Yu. Zhizhin; N. T. Kuznetsov (Тонкие химические технологии, 2022)
Objectives. One of the most promising methods of treating malignant tumors is 10B-neutron capture therapy. While compounds based on cluster boron anions [BnHn]2− (n = 10, 12) are often used as boron-containing agents due to the very high specific concentration of boron atoms per particle, the use of such compounds is associated with the need to develop new methods for the functionalization of boron clusters associated with the production of boron-containing derivatives containing biologically active functional groups. One of the most convenient methods of modification of [BnHn]2− (n = 10, 12) anions is the interaction of their derivatives containing cyclic oxonium-type substituents with negatively charged or neutral nucleophilic reagents. The disclosure of substituents of this type leads to the formation of closo-borates with functional groups separated from the cluster by an alkoxyl spacer chain. The purpose of this study is to develop methods for the synthesis of derivatives of the closo-decaborate anion [B10H10]2− with pendant nitrogen-containing groups.Methods. The general control of the reactions of the disclosure of cyclic substituents was carried out on the basis of 11B nuclear magnetic resonance (NMR) spectroscopy data. The structure of the obtained derivatives, including the nature of the attached functional groups, was determined using 1H, 13C attached proton test (APT) NMR and infrared (IR) spectroscopy data. The molecular weight of the synthesized compounds was confirmed by electrospray ionization mass-spectrometry (ESI–MS).Results. The interaction of the anion [2-B10H9O(CH2)4O]− with secondary amines (dimethylamine, dipropylamine, diallylamine, dibutylamine, diisobutylamine, morpholine, di-sec-butylamine) in an ethanol environment is investigated. As a result of the reactions, a cyclic substituent is shown to expand with the addition of a nucleophilic reagent. Seven new derivatives of the closodecaborate anion with pendant nitrogen-containing groups have been synthesized.Conclusions. A developed method for obtaining closo-decaborates with ammonium groups separated from the boron cluster by an alkoxyl spacer group is presented. It is shown that the use of amines of various structures does not fundamentally affect the course of the reactions, allowing the composition and structure of the target derivatives to be effectively regulated. The resulting compounds can be involved in further modification reactions due to a reactive pendant group, as well as being suitable for use as effective polydentate ligands. Closo-decaborates with pendant nitrogen-containing groups and their derivatives are of considerable interest in the synthesis of compounds for use in 10B-neutron capture therapy of malignant tumors.